Ultrasound of the Normal Brachial Plexus. Issue Volume 101:Issue S2(2017) (16th December 2017) - Simoni, Paolo; Ghassemi, Merhan; Le, Vinh Dat-Minh; Boitsios, Grammatina
Ultrasound (US) allows a reliable examination of the brachial plexus except for the spinal nerve roots, located deep in the neuro-foramina, beyond the shadowing of the transverse processes of the vertebral bodies. All the other fascicles of the brachial plexus can be mapped by US from the roots of the spinal cervical nerves, from C5 to T1 to the branches at level of the axillary region. US can be considered as an alternative to Magnetic Resonance Imaging (MRI) when MRI is contraindicated, not readily available or in case of claustrophobia. US can be used for the assessment of the brachial plexus in case of trauma, tumours and fibrosis induced by radiation oncology treatments. US is also a valuable tool to perform imaging-guided blocks of the brachial plexus. A prerequisite for a reliable US examination of the brachial plexus is knowledge of its complex anatomy. The operator is also required to learn the appropriate US views in order to have an optimal depiction of the brachial plexus, especially the areas where the bone structure's interposition makes the visualisation of the brachial plexus more arduous. The aim of this review is to provide the reader with the basics principles of the US normal anatomy and technique for a reliable mapping of the brachial plexus.